Synergistic Actions of Nisin, Sublethal Ultrahigh Pressure, and Reduced Temperature on Bacteria and Yeast - ter Steeg, Pieter F. (American Society for Microbiology, 1999)
Nisin in combination with ultrahigh-pressure treatment (UHP) showed strong synergistic effects against Lactobacillus plantarum and Escherichia coli at reduced temperatures (<15°C). The strongest inactivation effects were observed when nisin was present during pressure treatment and in the recovery medium. Elimination (>6-log reductions) of L. plantarum was achieved at 10°C with synergistic combinations of 0.5 μg of nisin per ml at 150 MPa and 0.1 μg of nisin per ml at 200 MPa for 10 min. Additive effects of nisin and UHP accounted for only 1.2- and 3.7-log reductions, respectively. Elimination was also achieved for E. coli at 10°C with nisin present at 2 μg/ml, and 10 min of pressure at 200 MPa, whereas the additive effect accounted for only 2.6-log reductions. Slight effects were observed even against the yeast Saccharomyces cerevisiae with nisin present at 5 μg/ml and with 200 MPa of pressure. Combining nisin, UHP, and lowered temperature may allow considerable reduction in time and/or pressure of UHP treatments. Kill can be complete without the frequently encountered survival tails in UHP processing. The slightly enhanced synergistic kill with UHP at reduced temperatures was also observed for other antimicrobials, the synthetic peptides MB21 and histatin 5. The postulated mode of action was that the reduced temperature and the binding of peptides to the membrane increased the efficacy of UHP treatment. The increases in fatty acid saturation or diphosphatidylglycerol content and the lysylphosphatidyl content of the cytoplasm membrane of L. plantarum were correlated with increased susceptibility to UHP and nisin, respectively.